Private or public information in foreign exchange markets? An empirical analysis - Dagfinn Rime (University of Oslo, Department of Economics, 2000)
In macroeconomic models of foreign exchange markets, exchange rates are determined by public information, while trading activities are completely irrelevant. In general, these models have low explanatory power for short horizons, which might be due to the possible existence of private information. Dealers in the foreign exchange market consider the order flow from customers to be the most important source of private information. I test a microstructural trading model incorporating private information, including both order flow and macroeconomic variables. The results show that order flow is an important variable for explaining weekly changes in exchange rates, thereby indicating an important role for private information.
Keywords: G15; F31; 330; Foreign Exchange; International Macroeconomics; Microstructure; Devisenmarkt; Informationsökonomik; Wechselkurstheorie; Mikrostrukturanalyse; Theorie